2004
DOI: 10.1007/s00384-004-0667-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma MMP-2 protein expression in lymph node-positive patients with colorectal cancer

Abstract: The MMPs we investigated were strongly elevated in tumour tissue compared with tumour-free bowel wall. Our results indicate that MMP-2 in plasma may possibly be used as a predictor in colorectal malignancy. The use of MMP-2 as a predicting tool in combination with different imaging techniques may give important preoperative information in patients with colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 19 publications
5
35
1
4
Order By: Relevance
“…This tendency is opposite to the results of Angenete et al who revealed that plasma levels of MMP-2 were higher in CRC patients with distant metastases [28]. However, our findings are in accordance with the study of Langenskiöld et al who found that plasma MMP-2 in CRC patients with T4 tumors was lower than in T3 and T2 subgroups [29]. The decrease of serum MMP-2 and TIMP-2 in more advanced tumor stages might reflect formation of MMP-TIMP complexes in colorectal tumor progression.…”
Section: Discussionsupporting
confidence: 62%
“…This tendency is opposite to the results of Angenete et al who revealed that plasma levels of MMP-2 were higher in CRC patients with distant metastases [28]. However, our findings are in accordance with the study of Langenskiöld et al who found that plasma MMP-2 in CRC patients with T4 tumors was lower than in T3 and T2 subgroups [29]. The decrease of serum MMP-2 and TIMP-2 in more advanced tumor stages might reflect formation of MMP-TIMP complexes in colorectal tumor progression.…”
Section: Discussionsupporting
confidence: 62%
“…[10][11][12][13][16][17][18][19] Moreover, our data indicated that conversion of the pro-form of MMP-9 to its active form, as represented by the ratio of the active MMP-9 to proMMP-9, was higher in tumour tissue. Although this finding was consistent with the majority of the studies mentioned above in which this ratio was investigated, Waas et al 11 and Moran et al 19 reported greater increases in the proform of MMP-9 than its active form during tumour progression in contrast to our finding.…”
Section: Discussionmentioning
confidence: 73%
“…Increased MMP-2, -9, -13 and decreased TIMP-1 was found to be significantly different between the patients with and without metastasis in prostate cancer (22). MMP-1, -2, -3, -7, -9 were elevated in colorectal cancers (23,24). Furthermore, Moran et al showed that a decrease in the MMP inhibitor TIMP-1 correlated with a poor outcome in colorectal cancer patients (24).…”
Section: Discussionmentioning
confidence: 99%